2019
DOI: 10.1021/acs.nanolett.9b00695
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Atomic-Scale Electrical Contact Quality Across Two-Dimensional Interfaces

Abstract: Contacting interfaces with physical isolation and weak interactions usually act as barriers for electrical conduction. The electrical contact conductance across interfaces has long been correlated with the true contact area or the "contact quantity". Much of the physical understanding of the interfacial electrical contact quality was primarily based on Landauer's theory or Richardson formulation. However, a quantitative model directly connecting contact conductance to interfacial atomistic structures still rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…As Φ interface and ρ carrier show opposite trends in affecting the local conductance comparison between AA and AB regions, it is not straightforward to combine the effects of Φ interface and ρ carrier on the moiré‐level modulation of local conductivity as measured by C‐AFM experiments. Atomic‐scale contact quality (ACQ) model, which takes both Φ interface and ρ carrier into consideration as described in our previous work for both graphene/metal and 2D material/2D material interfaces, was utilized here to unravel the modulation of conductance in twisted graphene systems. The individual C–C atom contact conductance ( G atomic )—C–C atom distance ( d C–C ) relationship used in the ACQ model is shown in Figure c (more details can be found in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As Φ interface and ρ carrier show opposite trends in affecting the local conductance comparison between AA and AB regions, it is not straightforward to combine the effects of Φ interface and ρ carrier on the moiré‐level modulation of local conductivity as measured by C‐AFM experiments. Atomic‐scale contact quality (ACQ) model, which takes both Φ interface and ρ carrier into consideration as described in our previous work for both graphene/metal and 2D material/2D material interfaces, was utilized here to unravel the modulation of conductance in twisted graphene systems. The individual C–C atom contact conductance ( G atomic )—C–C atom distance ( d C–C ) relationship used in the ACQ model is shown in Figure c (more details can be found in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Specically, there have been several CAFM studies where lateral force and current were measured simultaneously on atomically ordered surfaces. [7][8][9][10]27 In these experiments, both the current and lateral force patterns exhibited the same periodicity as the substrate's atomic lattice. Recently, such studies have shown that current can be used to detect defects in the surface lattice, 9,27 changes in conduction modes or pathways on the surface, 10 and stacking conguration of monolayers on the substrate.…”
Section: Introductionmentioning
confidence: 62%
“…1,2 Electrically conductive contacts are also relevant to topics such as the mechanical behavior of materials, 3 evolution of the contact formed between two bodies as they are pressed together, 4,5 and friction between sliding surfaces. [6][7][8][9][10] Such phenomena are studied using atomic force microscopy (AFM) which enables spatial, mechanical, and electrical measurements though small, well-dened contacts formed between a nanoscale AFM probe and a substrate. The electrical behavior of these contacts can be studied using conductive AFM (CAFM) where a potential bias is applied between a conductive probe and substrate and the current ow through the contact is measured.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations